RANCANG BANGUN ALAT PRAKTIKUM GLBB PADA BIDANG MIRING DENGAN PENGENDALI KEMIRINGAN BERBASIS ARDUINO - Wildan Jamil Khafidar Rochim; Wulandari, Rike Dwi; Nurul Aini Afida; Alfenda Dwi Andini; Ana Urifah Alwiyah (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2023)
There are lots of lessons learned at school, one of which is the study of glasses, these glasses are one of the sciences which study the basic elements that make up the universe. Therefore learning media, such as practicum tools are needed to explain imaginary physics concepts. This study aims to make a GLBB practicum tool on an inclined plane with an Arduino-based slope controller. This study uses the Research & Development (R&D) method. The design of this practicum tool has four stages, namely software design, programming and circuit sketching, hardware design, and testing the performance of the practicum tool that has been developed. This practicum tool uses several components such as Arduino Uno as the main controller, servo motor, infrared sensor, and LCD to display acceleration results. The calculation results show that the acceleration calculation and the automatic acceleration observation do have not much significant difference. This Arduino-based practicum tool can automatically measure the acceleration of objects on inclined surfaces when the angle is changed. The greater the angle formed, the greater the acceleration of the object.